Korean Mothers Attune the Frequency and Acoustic Saliency of Sound Symbolic Words to the Linguistic Maturity of Their Children - Jo, Jinyoung; Ko, Eon-Suk (Frontiers in Psychology, 2018)
The present study investigates Korean mothers’ use of sound symbolism, in particular expressive lengthening and ideophones, in their speech directed to their children. Specifically, we explore whether the frequency and acoustic saliency of sound symbolic words are modulated by the maturity of children’s linguistic ability. A total of 36 infant-mother dyads, 12 each belonging to the three groups of preverbal (M=8 months old), early speech (M=13 months old), and multi-word (M=27 months old) stage, were recorded in a 40-minute free-play session. The results were consistent with findings in previous research that the ratio of sound symbolic words in mothers’ speech decreases with child age and that they are acoustically more salient than conventional words in duration and pitch measures. We additionally found that mothers weaken the prominence for ideophones for older children in mean pitch, suggesting that such prominence of these iconic words might bootstrap infants’ word learning especially when they are younger. Interestingly, however, we found that mothers maintain the acoustic saliency of expressive lengthening constantly across children’s ages in all acoustic measures. There is some indication that children at age 2 are not likely to have mastered the fine details of scalar properties in certain words. Thus, it could be that they still benefit from the enhanced prosody of expressive lengthening in learning the semantic attributes of scalar adjectives, and, accordingly, mothers continue to provide redundant acoustic cues longer for expressive lengthening than ideophones.